Pengaruh Peringatan Bahaya Merokok Pada Kemasan Rokok Terhadap Minat Beli Mahasiswa Universitas Nuku di Kota Tidore Kepulauan - Nurjana Samad; Akbar A. Koja; M. jufri Sukandi (Jurnal Ilmiah Wahana Pendidikan, 2023)
Cigarettes are toxic substances that give a relaxing and suggestive effect. Cigarettes have a cylindrical shape of paper measuring between 70 and 120 mm long, with a diameter of about 10 mm which contains chopped tobacco leaves. Cigarettes are usually sold in boxes or paper packages that fit easily into pockets. Currently, cigarette packaging includes pictures of the impact of consuming cigarettes. The image that appears is the result after someone smokes too much. Cigarette packs also display the words "warning: Smoking Kills You" as a warning to cigarette users.The purpose of this study was to find out whether there is an effect of warnings about the dangers of smoking on cigarette packages on the buying interest of Nuku University students. The method in this study used quantitative methods with a population of 458 Nuku University students and used 94 samples calculated using the Slovin formula.The results of the analysis obtained interest, decided to buy, and the last stage was the interest of cigarette buyers of 0.207. The results of the correlation value can be seen that R^2 is 0.224. These results show that interest, deciding to buy, and the last stage have an impact on the interest in buying cigarettes in Nuku University students by 6.87%. The conclusion in this study is that cigarette packaging (image, cigarette brand, and price) has a significant effect on the intention to buy cigarettes by Nuku University students. The brand factor is the most important factor in considering students in making decisions to buy cigarettes.